IMPLEMENTASI PENYALURAN DANA BANTUAN SOSIAL DAN HIBAH DI KABUPATEN SIAK BERDASARKAN PERATURAN GUBERNUR RIAU NOMOR35TAHUN2017TENTANGPEDOMANBELANJAHIBAHDAN BELANJA BANTUAN SOSIAL YANG BERSUMBER DARI ANGGARAN PENDAPATAN BELANJA DAERAH - Hurul Aini; Mexsasai Indra; Zulfikar Jayakusuma (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
As a developing country, Indonesia is a country that has the fourth largest population in the world. With this large population, Indonesia must be more careful in the distribution of grants and social assistance so that there are no errors in the distributionin accordance with Riau Governor Regulation Number 35 of 2017 concerning Guidelines for Grants and Social Assistance Expenditures Sourced from Regional Revenue and Expenditure Budgets.This type of research can be classified as sociological juridical, namely a research approach related to the legal aspects of the subject matter to be discussed, with the reality on the ground. This research was conducted at the Social Service of Siak Regency, while the sample population was all parties related to the problem under study. Sources of data used are primary data and secondary data, data collection techniques in this study is by observation, questionnaires, interviews and literature review.In the results of the research problem there are three main things that can be concluded. First, the implementation of the distribution of grant funds in Siak Regency is classified as safe. The second implementation of the distribution of grant funds in Siak Regency is in accordance with Riau Governor Regulation No. 35 of 2017. The three administrative law enforcement efforts are to focus on recovering state or regional losses, in the case of determining the payment of replacement money in the form of money.Keywords : Implementation – Distribution – Bequest – Social Assistance